Normal human tissues, in addition to some tumors, express multiple different CD44 isoforms. - Fox, S; Fawcett, J; Jackson, D; Collins, I; Gatter, K; Harris, A; Gearing, A; Simmons, D (1994)
At least 20 different isoforms of the human CD44 lymphocyte-homing receptor/hyaluronan receptor have been described to date that arise from the differential splicing of up to 10 alternative exons (termed v1-v10) encoding the membrane-proximal extracellular domain. Although numerous analyses at the mRNA level have indicated tissue-specific expression of CD44 variants, few analyses have been performed at the protein level because of limited availability of suitable monoclonal antibodies. Recently, however, exon-specific monoclonal antibodies have been generated using bacterial fusion proteins, and these have been reported to detect high levels of vCD44 containing the v6 exon on human tumors. Together with earlier evidence linking this particular exon with tumor metastasis in the rat, these latter experiments have led to the interpretation that v6 splice variants play a causative role in tumor dissemination. In this paper we describe the use of a new and comprehensive panel of CD44 exon-specific monoclonal antibodies generated against a recombinant CD44(v3-10)-immunoglobulin chimera to study vCD44 expression in a large number of normal and neoplastic tissues. We show that the expression of vCD44 varies greatly among different human tumors and that some express either very low levels of vCD44 or no CD44 at all. Furthermore, we demonstrate that expression is not limited to isoforms containing the v6 exon but includes variants carrying v3, v4/5, and v8/9. Additionally, normal epithelial tissues are shown to express considerable levels of these same vCD44 isoforms. Such results argue against a ubiquitous role for vCD44 isoforms in promoting tumor growth and metastasis.